Boundary element method to the study of a Stokes flow past an obstacle in a channel - Kohr, M. (Archives of Mechanics, 1997)
In this paper the author gives an integral representation for the stream function and for the vorticity, corresponding to the problem of the Stokes flow past an obstacle in a channel. Using the Green's functions of the biharmonic equation and of the Laplace equation for the infinite horizontal strip, the above problem is reduced to a set of integral equations on the boundary of the obstacle. The boundary element method is used to solve these integral equations. The numerical results are given for the case of a circular obstacle.